Chapter 5 Ringwoodite its importance in Earth Sciences - Nestola, Fabrizio (De Gruyter, 2015)
The history of ringwoodite started in 1869 in a remote locality in the south-west of Queensland in Australia. Mr. Michael Hammond witnessed a meteorite shower close to the junction between Cooper and Kyabra Creeks (Lat. 25° 30S., Long. 142° 40E.),not far from Windorah (Queensland, Australia) and about 1000 km west of Brisbane. The meteorite fall was very impressive and in due course 102 stones were recovered. Mr. Hammond was the owner of the Tenham Station and from this the meteorite collection was named as "Tenham meteorites". This collection was then offered in 1935 to the British Museum by Mr. Benjamin Dunstan, formerly Government Geologist of Queensland.